Diversity of the entomofauna in a cocoa plantation (Theobroma cacao) in the municipality of Ilhéus, Bahia, Brazil - Garuzzo, Marlon dos Santos Pereira Birindiba Garuzzo; Pereira, Rosane Rodrigues da Costa (Pubvet, 2018)
The cocoa (Theobroma cacao) is the culture of economic interest in the southern region of Bahia. As a result of the 1990 crisis, caused by the fungus (Moniliophthora perniciosa), the crops were devastated, totally transforming the previously balanced environment. The objective of this work was to analyze the entomofauna in a cocoa plantation in Ilhéus, Bahia, territory affected by the pathogen, and verify the richness and abundance of the insects. A Pitfal trap of insects was collected in the area, identifying them at the family level and then evaluating the diversity. Insects belonging to five orders were found, with the most abundant being Hymenoptera (78.6%) and Coleoptera (15. 7%).The Formicidae family, of the order Hymenoptera, was more found in collection points, and a Coleoptera order, in a greater number of families. The diversity of insects measured by the Shannon Wienner index (SW), adapted for the family classification is 0.98.